Recent progress on phosphonium-based room temperature ionic liquids: Synthesis, properties, tribological performances and applications. (March 2022) - Rahman, Md Hafizur; Khajeh, Arash; Panwar, Pawan; Patel, Manish; Martini, Ashlie; Menezes, Pradeep L.
Abstract: Phosphonium-based room temperature ionic liquids (P-RTILs) offer outstanding lubricant properties. Studies have shown that the cationic chain length and anionic ring size significantly affect the performance of P-RTIL lubricants by altering properties, such as viscosity, density, thermal stability, wettability, and solubility. Functionalized moieties further improve their performance. However, the presence of halide groups could introduce corrosion and toxicity, which could be minimized by non-halide anions with large alkyl-chain-carrying cations to optimize both corrosion and tribological performance of P-RTILs. In this review, state-of-the-art research of P-RTILs is summarized from the lubrication perspective, covering their synthesis, properties, lubricant-relevant mechanisms, and performance matrices. Finally, the potential for developing a circular economy enabled by the biodegradability, recovery, and alternative applications of P-RTILs is discussed. Graphical Abstract: ga1 Highlights: Tribological properties and performance of phosphonium based ionic liquids (P-RTILs) have been summarized. Synthesis of P-RTIL lubricants has been illustrated through quaternization and ion exchange reactions. High viscosity and functionalized moieties favor P-RTILs to form tribo-film at a wide temperature range. Corrosion and tribo-corrosion could be restricted using halide free functionalized P-RTILs. Recent studies on the reusability and biodegradability of P-RTILs could potentially lead to sustainability.